Grit dan Self-Control pada Mahasiswa Fakultas Kedokteran - Jesslyn Antoinette Justine; Ellen Theresia (Universitas Kristen Maranatha, 2019)
This research was conducted with the aim of knowing the relationship between grit and self-control which is a variable that can predict the lecture process and achievement. The study was conducted on 114 active students of the